Relationship of Knowledge and Perception of Self-Medication of Cough Medicine to Lung Function Disorders in Construction Workers in Indonesia - Suryadinata, Rivan Virlando; Lorensia, Amelia; Rizki, Rahmat (Universitas Islam Bandung, 2023)
Construction workers were at high risk for chronic lung disease and decreased lung function, which often causes coughing symptoms. Self-medicated cough medicines were not only at risk for the incidence of side effects but also associated with the economy. This study aimed to determine differences in knowledge and perceptions about pulmonary function disorders. This study was an observational study using a case-control design conducted from April to December 2018. The subject was actively working in Rungkut subdistrict, Surabaya. Data will be presented descriptively, with relationships and differences analyzed using the chi-square test. Respondents found in both groups were 158, with 79 respondents in each group. Most of the respondents had a very high level of knowledge and perception in the group with impaired lung function (p=0.000). In addition, there is a relationship between knowledge and perception of self-medication of cough medicine. In conclusion, knowledge is related to construction workers' perception of self-medication of cough medicine.